PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI PEDAGOGIS GURU, SIKAP, AKTIVITAS TERHADAP HASIL BELAJAR - Lianti Isnani; I Komang Winatha; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2014)
The purpose of this research is to know whether there is influence in students’perceptions of teachers’pedagogical competence and attitude of students through activities on students’achievement of IPS Terpadu in class VIII of SMPN 4 Liwa Lampung Barat academic year 2013/2014. The method is descriptive verification. In order to test all hypotheses, it uses path analysis. The analysis shows that:(1)There is the influence of students’perceptions about  pedagogical competence of teachers in activities;(2)There is influence of students’attitudes toward activities;(3)There is direct influence on students’perceptions of pedagogical competence of teachers on achievement;(4)There is influence students’attitudes toward achievement;(5) There is activity influence on achievement;(6)There is influence of students’perceptions about the pedagogical competence of teachers on achievement through activities;(7)There is influence of students’attitudes toward achievement through activities;(8)There is influence of student’perceptions about pedagogical competence of teachers and students’attitudes together in activities;(9)There is influence of students’perceptions about the pedagogical competence of teachers and students’attitudes through activities on achievement.Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh persepsi siswa tentang kompetensi pedagogis guru dan sikap siswa melalui aktivitas terhadap hasil belajar IPS Terpadu siswa kelas VIII SMPN 4 Liwa Lampung Barat Tahun Pelajaran 2013/2014. Metode yang digunakan deskriptif verifikatif. Untuk menguji semua hipotesis menggunakan analisis jalur. Hasil analisis menunjukkan bahwa:(1)Ada pengaruh persepsi siswa tentang kompetensi pedagogis guru terhadap aktivitas;(2)Ada pengaruh sikap siswa terhadap aktivitas; (3)Ada pengaruh langsung persepsi siswa tentang kompetensi pedagogis guru terhadap hasil belajar;(4)Ada pengaruh sikap siswa terhadap hasil belajar;(5)Ada pengaruh aktivitas terhadap hasil belajar;(6)Ada pengaruh persepsi siswa tentang kompetensi pedagogis guru terhadap hasil belajar melalui aktivitas;(7)Ada pengaruh sikap siswa terhadap hasil belajar melalui aktivitas;(8)Ada pengaruh persepsi siswa tentang kompetensi pedagogis guru dan sikap siswa secara bersama-sama terhadap aktivitas;(9)Ada pengaruh persepsi siswa tentang kompetensi pedagogis guru dan sikap siswa melalui aktivitas terhadap hasil belajar.Kata kunci: aktivitas, persepsi siswa, sikap siswa.